LEONARD SWIDLER’S CALL TO INTER-RELIGIOUS DIALOGUE REVISITED - Preda, Alina (Journal for the study of religions and ideologies, 2024)
The aim of this article is to trace a brief history of the attempts that have been made to promote inter-religious dialogue, to outline the accomplishments to date, and to scrutinize both the current challenges posed to this project, and the future requirements to be met if worldwide interfaith cooperation is ever to be achieved. When investigating current inter-religious interactions, it is critical not to neglect the polemical dimension, but to establish the causes for the disagreements, and to effectively remove them. Given the inevitability of religious transmission within families, educational systems worldwide must offer exposure to multiple worldviews and belief systems that accurately reflect the diverse societies and cultures around the globe. In order to liberate themselves from the grip of fanatical thinking, the youth should not only be instructed in the teachings of a single religion, but also be exposed to the origins of humanity’s inclination towards religious beliefs and to the various ways in which these beliefs are expressed. This exposure, and the resulting newly-formed mentality will strengthen the response to Leonard Swidler’s call for the endorsement of a Universal Declaration of Global Ethics and, together with this indefatigable supporter of inter-religious co-operation, we will finally be able to genuinely proclaim that we are living in an Age of Global Dialogue.